2021
DOI: 10.1080/09575146.2021.1910799
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of factors affecting the baseline assessment scores of children attending morning or afternoon sessions in nursery settings in Wales

Abstract: To cite this article: Jane Dorrian (2021): An exploration of factors affecting the baseline assessment scores of children attending morning or afternoon sessions in nursery settings in Wales, Early Years,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…These disparities could affect the evidence that judgements are based upon. Other factors, such as time of day that the assessment happens, could also have an effect (Dorrian, 2021). With this in mind, it could be suggested that the scores linked to activity-based criteria are more reflective of the child's ability to settle into the new environment rather than their specific knowledge or skills, which again is dependent on the child's prior experiences.…”
Section: Administration Of the Assessmentmentioning
confidence: 99%
“…These disparities could affect the evidence that judgements are based upon. Other factors, such as time of day that the assessment happens, could also have an effect (Dorrian, 2021). With this in mind, it could be suggested that the scores linked to activity-based criteria are more reflective of the child's ability to settle into the new environment rather than their specific knowledge or skills, which again is dependent on the child's prior experiences.…”
Section: Administration Of the Assessmentmentioning
confidence: 99%